The Significance of MET Expression and Strategies of Targeting MET Treatment in Advanced Gastric Cancer - Liao, Haiyan; Tian, Tiantian; Sheng, Yuling; Peng, Zhi; Li, Zhongwu; Wang, Jingyuan; Li, Yanyan; Zhang, Cheng; Gao, Jing (Frontiers in Oncology, 2021)
Background Accurate assessment of predictive biomarker expression is critical in patient selection in clinical trials or clinical practice. However, changes in biomarker expression may occur after treatment. The aim of the present study was to evaluate the effects of chemotherapy on MET expression in gastric cancer (GC). Methods MET expression was examined immunohistochemically before and after treatment in 122 patients with unresectable or recurrent GC, and was evaluated according to H-score or the scoring criteria used in the MetMAb trial. MET gene amplification was assessed by chromogenic in situ hybridization (CISH). The antitumor effect of MET targeted therapy was investigated in human gastric cancer cells in vitro and in vivo, and the underlying molecular mechanisms were analyzed by western blot. Results MET expression was associated with Lauren classification as well as tumor differentiation by either scoring system. MET amplification was not associated with clinical characteristics. Of the 71 patients who had paired pre- and post-treatment tumor tissues, 28 patients (39%) were initially positive for MET expression, and 43 (61%) were negative. Twenty-five patients (35%) showed significant changes in MET expression after treatment (P=0.007). Additionally, there was a concomitant overexpression of MET and HER2 in a subset of GC patients. MET inhibitor volitinib could significantly inhibit cell proliferation and xenograft growth in vitro and in vivo in MKN45 cells with MET and phosphorylated MET (pMET) high expressions via suppressing downstream PI3K/Akt and MAPK signaling pathways. Furthermore, combination therapy targeting both MET and HER2 demonstrated a synergistic antitumor activity. Conclusions MET expression is altered post chemotherapy and MET status should be evaluated in real-time. Both MET and pMET expressions might need to be considered for patients suitable for volitinib treatment.